DIFFUSING THE PROBLEM: HOW ADOPTING A POLICY TO SAFELY STORE AMERICA’S NUCLEAR WASTE MAY HELP COMBAT CLIMATE CHANGE (Utah Environmental Law Review; Vol 28 No 2 (2008), 2009)
Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} Over the past several years, the problem of climate change (also known as global warming) has received significant attention from the public, media, and policymakers.   In connection with this increased attention, numerous proposals have been introduced to reduce the amount of carbon dioxide and other human-produced greenhouse gases that contribute to climate change.   One common proposal—both in the United States and internationally—is to move towards greater reliance on energy produced by nuclear power plants because of the fact that, unlike most traditional energy sources, nuclear energy results in the emission of little or no carbon dioxide.   One example of such a proposal is President George W. Bush’s call for an increase in the production of nuclear energy and the construction of new nuclear power plants, which he states will reduce carbon emissions and promote energy independence.